2016
DOI: 10.1088/1367-2630/18/5/053016
|View full text |Cite
|
Sign up to set email alerts
|

Current flow paths in deformed graphene: from quantum transport to classical trajectories in curved space

Abstract: In this work we compare two fundamentally different approaches to the electronic transport in deformed graphene: (a) the condensed matter approach in which current flow paths are obtained by applying the non-equilibrium Green's function (NEGF) method to the tight-binding model with local strain, (b) the general relativistic approach in which classical trajectories of relativistic point particles moving in a curved surface with a pseudo-magnetic field are calculated. The connection between the two is establishe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 72 publications
(149 reference statements)
1
89
0
Order By: Relevance
“…(A.10) and using the variables ξ and s defined in (43), we can obtain the following pair of Hamiltonians:…”
Section: A Wigner Function: Moyal -Productmentioning
confidence: 99%
“…(A.10) and using the variables ξ and s defined in (43), we can obtain the following pair of Hamiltonians:…”
Section: A Wigner Function: Moyal -Productmentioning
confidence: 99%
“…From Figs. 2(b) and 2(c) it is also clear that the deformation enhances the current in the region directly behind it, acting as a lens that focuses the current at this electron energy [56].…”
mentioning
confidence: 95%
“…At low energies and for large-scale deformations, which fulfill the hierarchy lattice constant wavelength deformation scale, the continuum and geometric optics approximations can be applied to the tight-binding Hamiltonian (1). In our previous work [29], we have shown that in that case the current flow in deformed graphene can be predicted by trajectories of relativistic massless fermions which move in a curved space in the presence of a pseudo-magnetic field…”
Section: B Current Flow Lines In the Geometric Optics Approximationmentioning
confidence: 98%
“…1. The finite curvature expressed by the local frame e a (x) also affects significantly the transport [29]. However, it acts equivalently on the two valleys and hence has no effect on the valley polarization.…”
Section: A the Effective Dirac Equation In Curved Spacementioning
confidence: 99%